Analysis of octenylsuccinate rice and tapioca starches: Distribution of octenylsuccinic anhydride groups in starch granules. (15th November 2016) - Whitney, Kristin; Reuhs, Bradley L.; Ovando Martinez, Maribel; Simsek, Senay
Highlights: Microscopy showed that esterification occurs mainly on the granule surface. Amylopectin structure changed significantly due to the esterification process. 1 H NMR spectra indicated that OSA groups were mainly located on the amylose chains. Abstract: Characterization of the fine structure of octenylsuccinic anhydride (OSA) starch would lead to a better understanding of functional properties. OSA rice and tapioca starches were analyzed using microscopy, liquid chromatography and nuclear magnetic resonance. Chain length distribution of amylopectin changed significantly (P < 0.05) after OSA esterification. Weight averaged degree of polymerization (DPw ) decreased significantly (P < 0.05) from 16.47 to 13.29 and from 14.87 to 12.47 in native and OSA rice and tapioca starches, respectively. The chain length distribution of pure amylopectin fractions suggested that OSA groups were not present in the amylopectin portion of the starch. 1 H NMR analysis of pure amylose and amylopectin fractions indicated that OSA substitution was present only in amylose fractions of rice and tapioca starches. Esterification with 3% OSA results in starch that has OSA substituted mainly on amylose chains or possibly on amylopectin chains that have been hydrolyzed from the amylopectin molecules during esterification.